(untitled) (Revista Apotheke, 2025)
Interview conducted with the Portuguese professor, artist, and researcher Teresa Torres de Eça in January 2020, as part of a Postdoctoral investigation in Fine Arts entitled “The studio as a space of production in the formation of the teacher-artist.” The aim was to broaden discussions on the processes of intersection between art and teaching in the constitution of the teacher-artist, based on the interviewee’s experiences. The conversation took place in her studio, a space she describes as a chapel of introspection, creation, and experimentation. Teresa reflected on the concept of the minor artist, on teaching as a relational artistic practice, understood as “being together” with students and the community as an act of creation, and emphasized the importance of maintaining an artistic practice for the well-being, identity, and legitimacy of art teachers. The dialogue also highlighted how the studio can be conceived as a place where art, teaching, and research converge.